2020
DOI: 10.1111/ijsw.12425
|View full text |Cite
|
Sign up to set email alerts
|

Equity in sustainable development: Community responses to environmental gentrification

Abstract: Sustainable development aims to address economic, social, and environmental imperatives; yet, in practice, it often embodies a neoliberal market logic that reinforces inequalities. Thus, as the social work profession grapples with its role in advancing environmental sustainability, practice models must explicitly attend to social and economic justice. For example, environmental gentrification refers to situations in which the cleanup of contaminated land or the installation of environmental amenities intention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 52 publications
0
19
0
2
Order By: Relevance
“…We imported records into EndNote (Clarivate Analytics, Beijing, China) for coding and management. Second, from the above searches, we identified five systematic reviews that focused on either gentrification and health [8][9][10]33] or ways to limit environmental gentrification [34]. Following the example of previous scoping reviews [29], we screened their references to identify additional relevant articles that met the inclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
“…We imported records into EndNote (Clarivate Analytics, Beijing, China) for coding and management. Second, from the above searches, we identified five systematic reviews that focused on either gentrification and health [8][9][10]33] or ways to limit environmental gentrification [34]. Following the example of previous scoping reviews [29], we screened their references to identify additional relevant articles that met the inclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
“…We also found that although respondents agreed that gentrification and displacement are problems for some residents, most questioned the organization’s collective ability to prevent these problems or wondered whether prioritizing housing issues would dilute their mission. There are unquestionably limitations to the power of local organizing in a globalizing world (DeFilippis et al, 2010); however, siloing urban greening without also tending to development and affordable housing can contribute to environmental gentrification (Krings & Schusler, 2020; Rigolon & Németh, 2018). By focusing on the natural environment and neglecting Pilsen’s affordable housing issue, PERRO may align more closely with the philosophy of environmentalism, rather than an environmental justice logic that integrates a holistic understanding of what it means to live in a healthy community (Pezzullo & Sandler, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Second, community practitioners should use an intersectional rather than siloed approach to issue selection (Krings & Schusler, 2020). This is particularly important because organizations that improve the natural or built environment of a neighborhood also risk contributing to gentrification and displacement of people intended to benefit from their efforts, thus increasing segregation and inequality (Dale & Newman, 2009).…”
Section: Implications For Community Practicementioning
confidence: 99%
“…28 Krings and Schusler define environmental gentrification as ''situations where improvements to environmental quality increase real estate prices, contributing to the displacement of vulnerable residents.'' 29 Consequently, environmental gentrification can occur when Brownfields are cleaned up or when gardens and parks are established in urban areas. 30 Amorim Maia et al add that in addition to displacement, the most economically vulnerable, who are often those impacted, also may find themselves segregated from access to the benefits of green development.…”
Section: Advocacy: Policy As Harm Reduction and Supporting Community Grassroots Spacesmentioning
confidence: 99%
“…29 Consequently, environmental gentrification can occur when Brownfields are cleaned up or when gardens and parks are established in urban areas. 30 Amorim Maia et al add that in addition to displacement, the most economically vulnerable, who are often those impacted, also may find themselves segregated from access to the benefits of green development. 31 Checker goes on to say that environmental gentrification is the result of the ''convergence of urban redevelopment, ecologically minded initiatives and environmental justice activism in an era of advanced capitalism.''…”
Section: Advocacy: Policy As Harm Reduction and Supporting Community Grassroots Spacesmentioning
confidence: 99%